Технологія відновлення функціонального стану студентів в умовах обмеженого простору - Дегтярьова, Ірина Вікторівна; Церетелі, Вікторія Олександрівна; Гасан, Юлія Миколаївна (Прикарпатський національний університет імені Василя Стефаника, 2023)
Мета роботи – визначити ефективність запропонованої технології відновлення функціонального стану студентів, котрі опинилися в умовах обмеженого простору через пандемію, воєнний стан у країні або неможливість користування запропонованими засобами фізичної активності за межами одного приміщення. Методи дослідження. Для визначення функціонального стану студентів використовували опитувальники (ступінь хронічного стомлення та гострого фізичного стомлення), та визначення фізіологічних резервів організму студента за індексом Руф’є. Результати. Запропоновано під час дистанційного навчання, коли студенти більшу часу проводять в обмеженому просторі, для підтримання та поліпшення функціонального стану, виконувати вправи з фітнес-йоги, включати психоемоційне тренування та на протязі доби робити рухові хвилини. Виявлено рівень стомлення та функціонального стану студентів експериментальної групи на початку та у кінці експерименту, після застосування розробленої технології. Встановлено залежність функціонального стану від рухової активності. Висновки. Доведена ефективність застосування розробленої технології відновлення функціонального стану студентів в умовах обмеженого простору.

The goal of article – to determine the effectiveness of the proposed technology for restoring the functional state of students who found themselves in conditions of limited space due to the pandemic, war state in the country or impossibility of using the proposed means of physical activity outside the same premises. Вased on the study of a group of students, the connection between the functional state of students before and after the exercises will be revealed, and it will be possible to draw the necessary conclusion. Research methods. Questionnaires were used to determine the functional state of the students (degree of chronic fatigue and acute physical fatigue), and to determine the physiological reserves of the student’s body according to the Ruffier index. The Ruffier index is an indicative method for studying the functional state of students, because it is directly related to the training of the body and its indicator indicates the general physical state of a person. If these indicators, for example, are below the norm, then this indicates insufficient physical training and may serve as contraindications for attending physical education classes or any physical activity in general. If, on the contrary, the indicators are above the norm, then this may indicate, for example, a malfunction of the heart. Results. It is suggested during distance learning, when students spend more time in a limited space, to maintain and improve their functional state, to perform fitness yoga exercises, to include psycho-emotional training and to do movement minutes during the day. The level of fatigue and functional state of the students of the experimental group at the beginning and at the end of the experiment, after using the developed technology, was revealed. The dependence of the functional state on motor activity was established. Correct adaptation is an important factor in the functional state. In general, we understand the process of adaptation as a complex system of transformations that occur with a person in accordance with changes in his life conditions, as a result of which certain qualities arise: first, adaptability as a direct result of these transformations, that is, the state of matching existing qualities and requirements of the environment; secondly, adaptability as an integrated personal quality that ensures a person’s ability to further transformations. The result of the adaptation process is the adaptation of a person to a certain system. Conclusion. Рhysical activity directly affects the functional condition of students and their general physical condition, improves mental activity, contributes to increasing efficiency and energy even in a limited space. The effectiveness of the application of the developed technology for restoring the functional state of students in conditions of limited space have been proven. It’s very important for a student to be able to independently organize his studies, prioritize tasks and feel comfortable in the mental aspect. A motivated student will be able to effectively divide his working day and time and find some time for physical activity to improve his well-being.
Keywords: фізична активність; здоров'я; спорт; фізична культура; дистанційне навчання; students; physical activity; technology; limited space; health; functional state